EFEKTIFITAS PROGRAM COMMUNITY MENTAL HEALTH NURSING (CMHN) DALAM MENURUNKAN STIGMA GANGGUAN JIWA DI KOMUNITAS: LITERATURE REVIEW - Risa Farida; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The social stigma associated with mental health disorders is a major barrier that limits individuals’ access to healthcare services and hinders recovery efforts within the community, requiring a fundamental transition from an institutional care paradigm to a model based on a community-based approach. The Community Mental Health Nursing (CMHN) Program has been recognized as an important nursing intervention capable of effectively reducing social stigma. This review aims to synthesize empirical evidence regarding the effectiveness of the Community Mental Health Nursing Program in efforts to reduce the stigma surrounding mental health disorders in the community. This systematic literature review was conducted using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) framework. A comprehensive literature search was carried out in five leading databases: Scopus, PubMed, ScienceDirect, Google Scholar, and SINTA, focusing on publications from 2015 to 2025 using a structured combination of keywords (e.g., CMHN, stigma). The independent screening process resulted in 20 articles that met the inclusion criteria, which were then assessed for quality before the final synthesis. The review revealed that the Community Mental Health Nursing Program consistently shows substantial effects in reducing public stigma toward individuals with mental disorders (ODGJ). The effectiveness of the Community Mental Health Nursing Program is achieved through two main mechanisms: First, the training of Mental Health Cadres, which improves mental health literacy within the community. Second, the facilitation of direct and structured interactions (such as home visits and support groups) aligns with the Social Contact Theory (Corrigan, 2020), in which positive interpersonal contact serves to reduce prejudice. Evidence indicates that collaborative and educational elements represent the most influential factors contributing to the effectiveness of the program. The Community Mental Health Nursing Program is an evidence-based, empirically validated strategy aimed at combating the stigma associated with mental disorders. Clinical and policy implications highlight the need to strengthen interactive and collaborative Community Mental Health Nursing interventions, as well as to standardize instruments for measuring stigma outcomes to ensure comparability of findings in future research efforts.